Estudio técnico económico de una recicladora de neumáticos usados, para evitar la contaminación en la provincia de Cotopaxi. - Mena Estrella, Karol Esthefanía. (2021)
The objective of this research work is; to carry out an economic technical study of the used tires recycler in the Cotopaxi province, for the purpose research it has been made statistical tables of the environmental impact, as well as the possible suppliers, such as: techno centers , vulcanizing and generating entities of special waste, giving as resulting in the canton there is not an adequate process to dispose of tires, there are a lot of tires that are discarded to different inappropriate places, the technical study allowed to present the determination of the optimal location size plant. The engineering project, the administrative analysis and the development oand functional organization chart, in addition, it was located the place of the project, in the Cotopaxi province, Latacunga canton, Poaló parish, Pilligsillí neighborhood, North sector, 500 meters from the central church. Taking account the accessibility of basic services, roads and other services required for the recycler operation. However, an analysis of the technological options was carried out, to develop new artisanal products, extract the wire as scrap metal for that, a plant capacity was estimated in the daily production process, defining the comprehensive management process of used tires, that indicates the consecutive steps of recycling and based on this, the equipment, machinery, facilities necessary for the project , therefore, the investment and operating costs required must be identified. As well as the working capital, warehouse and machineries in the production area.